Inventory and identification of kana (Canna spp.) in Deli Serdang and Serdang Bedagai regency - maulida khairiza nawar; Emmy Harso Kardhinata; Eva Sartini Bayu (Jurnal Agroekoteknologi, 2018)
Inventory and identification of kana (Canna spp.) in Deli Serdang and Serdang Bedagai regency. Supervised by Ir. E. Harso Kardhinata, M.Sc., and Ir. Eva Sartini Bayu, MP., The purpose of the research is to inventory and identify of kana (Canna sp.) in Deli Serdang and Serdang Bedagai regency. The research was conducted in Deli Serdang and Serdang Bedagai regency from February to March 2017, The research was dessigned by descriptive methode and the samples were collected based on accidental sampling technique. Morfological characteristic of kana were identified based on Tanaka (2001). The result showed that there were 11 genotip of kana are genotip genotip A, genotip B, genotip C, genotip D, genotip E, genotip F, genotip G, genotip H, genotip I, genotip J, gnotip K, based on identified by Tanaka (2001) is that genotip A as C. flaccid, genotip B as C. ‘King Humbert’, genotip C as C. edulis, genotip D as C. pedunculata, genotip E as C. cleopatra, genotip F as C. glauca, genotip G as C. jacobiniflora, genotip H as C. ‘Bengal Tiger’, genotip I as C. liliiflora, genotip J as C. discolour, genotip K as C. indica.. Some specieses of kana grow wild and have not been cultivated by community except C. indica and C. edulis. Keywords : identification, inventory, kana, morphological characteristics